Aluminum Containing Dendrimeric Silica Nanoparticles as Promising Metallocene Catalyst Supports for Ethylene Polymerization. Issue 17 (26th July 2018) - Cecílio, Duarte M.; Fernandes, Auguste; Lourenço, João Paulo; Ribeiro, M. Rosário
Abstract: Several aluminum containing dendrimeric silica nanospheres, DSAl materials, were prepared using different synthesis and post‐synthetic procedures. These materials were used for the immobilization of Cp2 ZrCl2 via direct impregnation. The support materials were rigorously characterized by TEM, N2 adsorption, FTIR (using pyridine as probe molecule) and SS‐NMR to assess their morphological, textural and surface acidic properties. Supported catalysts were tested in ethylene homopolymerization using methylaluminoxane (MAO) as co‐catalyst and scavenger. The relationships between the types and strength of acid sites, as well as the textural and morphological parameters of DSAl materials with the behavior of catalytic systems are explored in this work. The results analyzed in this paper confirm the importance that support surface acidity plays in the formation of the active species for ethylene polymerization and in its activity without neglecting the contribution of support textural properties as well. Abstract : Do acidity and textural features matter? Acidity has a critical role in the ethylene polymerization activity of zirconocene dichloride supported on Al‐containing dendrimeric silica nanospheres. However, the textural properties of the non‐conventional porous structure supports should not be neglected.